The Role of Open- Book Management in the Reduce of Administrative Errores: An analytical study of the opinions of a sample of managers at the Ministry of Municipalities and Tourism’s main Office and anumber of its directorates in the city of Erbil - Razaw Abdulkhaleq Hussein (QALAAI ZANIST JOURNAL, 2020)
The aim of the research is to identify the role open-book management with its subdivisions (Organazational Commitment, Organazational Performance, Specific rules for action) in reducing administrative errors. The research presented theoretical and conceptual framework for the main and secondary variables. Ministry of Municipalities and Tourism’s main office and number of its directorates were chosen as a field for conducting the research. The importance of the research stems from the importance of the topics examined. The research was systematically and descriptively analyzed, and a set of hypotheses was identified as probative responses to the research problem, which were tested using multiple statistical tools, using the SPSS-V.20 statistical program. The questionnaire was used as a means of obtaining the data. It was distributed to a sample of managers Ministry of Municipal’s main office and number of its directorates. The number of managers was 85, and 75 questionnaires were retrieved and all were valid for analysis. The study concluded that there is a relationship and influence for all dimensions of open-book management in reducing administrative errors. The research recommended employing this relationship to serve the Ministry of Municipalities and Tourism’s main office and number of its directorates to maintain the high levels of both dimensions of open-book management in order to reduce administrative errors.